Dental Fluorosis according to Birth Cohort and Fluoride Markers in an Endemic Region of Colombia - Saldarriaga, Alexandra [UNESP]; Restrepo, Manuel; Rojas-Gualdrón, Diego F.; Carvalho, Thamyris De Souza; Buzalaf, Marilia Afonso Rabelo; Santos-Pinto, Lourdes [UNESP]; Jeremias, Fabiano [UNESP] (Hindawi, 2021)
Objectives. To analyze changes in the dental fluorosis (DF) incidence according to a birth cohort and explore current exposure to DF in a case series. Methods. Repeated cross-sectional study of two periods: 2015 and 2018. Two standardized examiners registered DF using the Thylstrup-Fejerskov index in permanent teeth of children aged 7-18 years. Period and birth cohort frequencies were estimated by a generalized linear model, binomial family, and logarithmic link function. Period estimates are presented as prevalence ratios (PR) and birth cohort estimates as cumulative incidence ratios (RR); 95% confidence intervals and P values are reported. In a subsample of 37 volunteers (12.29 ± 2.63 years), the fluoride (F) concentration in toenails was measured using the HMDS diffusion method and an ion-specific electrode. Other samples from the local environment such as food, soil, and coal were also collected. Results. In 274 children, we found that nonsignificant increases between periods (PR = 1.17; 95% CI: 0.89-1.55) were not explained by birth cohort effects. A total of 37.8% of the subsample had a toenail F concentration ≥2 μg F/g. The salty snacks and seasoning had the highest F concentrations among local environmental samples. Conclusion. In this population with a high DF frequency according to birth cohort and the evaluated period, the study of soil, coal, and food samples indicated a continued F exposure. F concentration found in the toenails shows a moderate F exposure; nearly a third of the children and adolescents exceeded the adopted threshold of 2 μg F/g. It is important to monitor and explore changes in exposure in highly affected population.